The Incidence and Value of Planning Obligations - Rowley, Steven; Crook, A. (John Wiley & Sons, 2016)
This chapter examines the evidence of the growth, incidence and value of planning obligations. It reviews some of the early evidence on the growth of obligations and analyses in detail the first national studies of England undertaken by the author and colleagues on the incidence and value of obligations between 2003–2004 and 2007–2008 as well as a more recent study for 2010–2011. This chapter describes the methods used to collect data on obligations from local planning authorities and to value financial and in-kind obligations, including creating regional and national estimates of the total value agreed between local authorities and developers. Also looking at the incidence and value of all obligations, the chapter looks in detail at the incidence and value of the new affordable homes that were secured through planning obligations. It also examines who pays for the obligations agreed, whether landowners, developers or those buying completed developments